STUDENTS’ PERSPECTIVE ON KETRAMPILAN WAJIB BAHASA INGGRIS IN UNIVERSITAS MURIA KUDUS - Nuraeningsih Nuraeningsih (Universitas Muria Kudus, 2019)
Due to globalization, the need of English mastery is getting higher. Therefore, it is very important for students to master the international language in order to survive in the global competition. To prepare its alumni with good English competence Universitas Muria Kudus requires all students to pursue Ketrampilan Wajib Bahasa Inggris (English Compulsory Skill) with 0 SKS. This policy has been ruled since 2001 and organized by Language Center of Universitas Muria Kudus. To know whether the program runs effectively, at the end of each semester, there is an evaluation conducted by the instructors along with the head of the Language Center. However, it does not involve the students. Therefore, it is worthy to investigate students’ responses and opinions of the class. This study aims at describing students' perceptions on the learning process of Ketrampilan Wajib Bahasa Inggris in the academic semester of 2014/2015. To achieve the above objectives, this study was conducted by survey. Questionnaires were distributed to 98 students who were selected randomly, out of 498 students joining the class in the academic year 2014/2015. The results of data analysis shows that the learning process of Ketrampilan Wajib Bahasa Inggris class in odd semester academic year 2014/2015 ran well. This is shown from the learning strategies, learning media, learning materials, student interests, students discipline in joining the English course and student mastery were classified as good. Some improvements need to be done so that the quality of learning can be improved due to satisfactory service of Language Center.Keywords: Ketrampilan Wajib Bahasa Inggris, learning, TOEFL.